2021
DOI: 10.3390/en14196056
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Thermal-Hydraulic Performance and Optimization of Compact Heat Exchangers

Abstract: Heat exchangers play an important role in power, the chemical industry, petroleum, food and many other industrial productions, while compact heat exchangers are more favored in industrial applications due to their high thermal efficiency and small size. This paper summarizes the research status of different types of compact heat exchangers, especially the research results of heat transfer and pressure drop of printed circuit heat exchangers, so that researchers can have an overall understanding of the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 200 publications
(222 reference statements)
0
1
0
Order By: Relevance
“…It was reported in the work that at Reynolds numbers between 1,000 and 1,300, there was a transition from laminar to turbulent flow. Another experimental study to determine the thermal-hydraulic performance in the transition flow of water in induced and plain tubes was carried out by another researchers [13]. The study's findings confirmed that transition occurred earlier in the induced tube.…”
Section: Introductionmentioning
confidence: 80%
“…It was reported in the work that at Reynolds numbers between 1,000 and 1,300, there was a transition from laminar to turbulent flow. Another experimental study to determine the thermal-hydraulic performance in the transition flow of water in induced and plain tubes was carried out by another researchers [13]. The study's findings confirmed that transition occurred earlier in the induced tube.…”
Section: Introductionmentioning
confidence: 80%